If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (4a + 8x)(7a + -5x) = 0 Multiply (4a + 8x) * (7a + -5x) (4a * (7a + -5x) + 8x * (7a + -5x)) = 0 ((7a * 4a + -5x * 4a) + 8x * (7a + -5x)) = 0 Reorder the terms: ((-20ax + 28a2) + 8x * (7a + -5x)) = 0 ((-20ax + 28a2) + 8x * (7a + -5x)) = 0 (-20ax + 28a2 + (7a * 8x + -5x * 8x)) = 0 (-20ax + 28a2 + (56ax + -40x2)) = 0 Reorder the terms: (-20ax + 56ax + 28a2 + -40x2) = 0 Combine like terms: -20ax + 56ax = 36ax (36ax + 28a2 + -40x2) = 0 Solving 36ax + 28a2 + -40x2 = 0 Solving for variable 'a'. Factor out the Greatest Common Factor (GCF), '4'. 4(9ax + 7a2 + -10x2) = 0 Factor a trinomial. 4((7a + -5x)(a + 2x)) = 0 Ignore the factor 4.Subproblem 1
Set the factor '(7a + -5x)' equal to zero and attempt to solve: Simplifying 7a + -5x = 0 Solving 7a + -5x = 0 Move all terms containing a to the left, all other terms to the right. Add '5x' to each side of the equation. 7a + -5x + 5x = 0 + 5x Combine like terms: -5x + 5x = 0 7a + 0 = 0 + 5x 7a = 0 + 5x Remove the zero: 7a = 5x Divide each side by '7'. a = 0.7142857143x Simplifying a = 0.7142857143xSubproblem 2
Set the factor '(a + 2x)' equal to zero and attempt to solve: Simplifying a + 2x = 0 Solving a + 2x = 0 Move all terms containing a to the left, all other terms to the right. Add '-2x' to each side of the equation. a + 2x + -2x = 0 + -2x Combine like terms: 2x + -2x = 0 a + 0 = 0 + -2x a = 0 + -2x Remove the zero: a = -2x Simplifying a = -2xSolution
a = {0.7142857143x, -2x}
| -1(x-y)+3(y-x)= | | (2w+2b)(3w+5b)= | | (ln(4)^2/(2ln2)-(ln(2)^2)/(2ln2) | | 30=3x-9 | | 2lnx-6=0 | | -5=0.25(4t+20r)-8r | | 1-4x/2x-1 | | 8sinx+16=20 | | t(2+-5t+3t^2)=0 | | 8+3x=x | | n^2+4n+16=0 | | 15z-(-3x-10x)= | | 2x^2+28=1 | | 3x-5y=42 | | n^3-64=0 | | X-0.6x=12 | | h^2+6h+9= | | 3x^2-60x+400=0 | | 7a+4b=32 | | 3(2x-4y)-2(2x-5y)+2y= | | ln(4x+5)=ln(2x-1)+ln(3) | | x+(x+1)+(x+2)+(x+3)=66 | | 2x+96-0= | | 4y+3=14 | | 38x+5y= | | 4y+4x-xy=0 | | 2p^2-2p/7p-7= | | Sqrt[x]=30 | | x-4y-12=0 | | dx+x(lnx-lny-1)dy=0 | | x^2-2x=-1/2 | | 3x+3y=132 |